Preparation of double-metal cyanide catalysts with H3Co(CN)6 for propylene oxide homo- and CO2-copolymerization - Seo, Yeong Hyun; Hyun, Yong Bin; Lee, Hyun Ju; Baek, Jun Won; Lee, Hong Cheol; Lee, Jung Hyun; Lee, Junseong; Lee, Bun Yeoul (Journal of CO2 Utilization, 2021)
A preparative-scale (100 g scale) synthesis of H3Co(CN)6 was achieved, the structure of which was unambiguously determined using X-ray crystallography. Double-metal cyanide complexes (DMCs) were facilely prepared with the prepared H3Co(CN)6; mixing H3Co(CN)6 and Zn(EH)2 (EH = 2-ethylhexanoate) in methanol precipitated solids, which were used for polymerization after solvent removal. The prepared DMCs exhibited good activity in PO homopolymerization even in the presence of a propylene glycol (PG) starter. A conventional DMC prepared by the salt metathesis reaction of K3Co(CN)6 with ZnCl2 in water was inactive in the presence of such a simple PG starter. The prepared DMC was also active in PO/CO2 copolymerization, although its productivity was substantially lower under CO2 pressure. The carbonate linkage fraction was high (FCO2 = 0.48–0.66, depending on the CO2 pressure), although the generation of a small amount of cyclic carbonate was inevitable (∼10 wt%). However, feeding a starter, such as polypropylene glycol (PPG) or adipic acid, to obtain low-molecular-weight macrodiol deteriorated the catalytic performance. A substantial amount of cyclic carbonate was concomitantly generated (∼30 wt%).
Keywords: Copolymerisation; Cyclic carbonates; Double metal cyanide catalysts; Double metal cyanides; Double-metal cyanide complex; Hydrogen hexacyanocobaltate; Metal cyanide complexes; Propylene glycols; Propylene oxide; Solvent removal; CO2; Copolymerization; Double-metal cyanide complex; Hydrogen hexacyanocobaltate; Propylene oxide